A Dynamic Analysis of Regulation and Productivity in Retail Trade - Florin Maican; Matilda Orth (Research Institute of Industrial Economics (IFN), 2012)
Liberalization is widely recognized to drive productivity growth. Retail trade is often thought to substantially contribute to the frequently debated productivity gap between Europe and the U.S. In Europe, entry regulations empower local authorities to decide on the entry of new stores. We use a dynamic structural model and data on all retail stores in Sweden during the period 19962002 to quantify the effect of entry regulations on productivity in retail. The results show that the approval of an additional application by local authorities increases median productivity by approximately 2 percent in most subsectors. A stricter regulation in terms of one fewer approved application in each local market corresponds to an annual economic cost for the retail trade sector of nearly 10 percent of total annual capital investments. Our findings suggest that a restrictive entry regulation limits the role of entry and exit in local market dynamics and productivity growth.
Keywords: L11; L81; L88; O30; 330; Retail Trade; Regulation; Imperfect Competition; Dynamic Structural Model; Productivity Decomposition